Assessing Speaking Skills through Picture Description: Evidence from Senior High Students - Afrizal, Johari; Ayoddukki, Mumlikka; Yulianto, Yulianto (Journal of English Language and Education, 2025)
This study investigated the speaking skills of senior high school students in Pekanbaru, Riau, Indonesia, through a picture description task. Speaking is a crucial skill in English as a Foreign Language (EFL) learning because it enables effective communication in both academic and social contexts. However, despite its significance, limited research has examined Indonesian students’ speaking performance through picture description tasks, particularly in relation to pronunciation and fluency. To address this gap, the present study assessed 46 students using a standardized rubric covering comprehension, grammar, vocabulary, pronunciation, and fluency. Their performances were evaluated by three independent raters to ensure reliability and objectivity. The findings showed an overall mean score of 3.7, categorized as very good. Vocabulary obtained the highest average (4.2), followed by comprehension (3.8), grammar (3.6), and fluency (3.5). Pronunciation recorded the lowest mean (3.3). These results highlight the need for targeted pedagogical strategies to improve pronunciation and fluency while consolidating vocabulary and comprehension skills.